The Iglesia Filipina independiente's (IFI) opposition to development aggression in the province of Iloilo. - Peraman, Smile C.
This study aims to identify and determine the effectiveness of the Iglesia Filipina Indenpendiente's opposition to development aggression cases in the Province of Iloilo, Philippines. This provides better understanding on the effectiveness of the actions and strategies of IFI on the issues they oppose, specifically development aggression., The study found out that Iglesia Filipina Independiente is not effective in opposing development aggression in the Province of Iloilo. It was established that the stance of IFI on development aggression is based on their history as instrument of the oppressed society during the Philippine Revolution; and on their writings such as the bible and articles of religion. The identified development aggression cases opposed by IFI in the province produce undesirable impacts to the church, community, and to the environment. Thus, with the strategies employed by IFI (media advocacy , grassroots organizing, coalition-building and lobbying), the study found out that out of five (5)cases of development aggression opposed by IFI in the province, three(3) are pursued and only two(2) are discontinued. With this it was proven that IFI is not effective in demonstrating it opposition to development aggression in the province of Iloilo.